Chitosan Concentration in Aqueous Media via Electrical Conductivity - Sarka Evzen*; Petra Smrčková; Evren Gölge (Trends in Computer Science and Information Technology, 2025)
Abstract Chitosan is the deacetylated polymer of chitin. Chitosan has many advantageous properties such as biodegradability, biocompatibility, nontoxicity, and hydrophilicity. It is also antioxidant, antimicrobial, renewable, and low-cost. The properties and potential uses of chitosan have been of great interest to researchers for many years. Chitosan has limited solubility in neutral and alkali solutions. Many methods to quantify the chitosan concentration have been proposed i.e. UV–vis spectrophotometry, fluorspectrophotometry, cathodic stripping voltammetry, High-performance Liquid Chromatography (HPLC), and resonance Rayleigh scattering method. This paper proposed a practical non-invasive method for determining chitosan content in low-pH aqueous media.